A Note on the Theory of Price Index Numbers - Lerner, A. P. (Review of Economic Studies, 1935)
Journal Article A Note on the Theory of Price Index Numbers Get access A. P. Lerner A. P. Lerner London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 1, October 1935, Pages 50–56, https://doi.org/10.2307/2967571 Published: 01 October 1935